A self-repairing composite pipe and preparation method thereof
By using a three-layer structure of self-healing composite pipes, combined with materials such as high-content PVC resin, polyetheramine and closed polyurethane, the problem of easy scratches and cracking of PVC pipes is solved, achieving self-healing effects and high performance at normal temperatures. Bonding strength.
Patent Information
- Application Number
- CN202411509999.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-28
AI Technical Summary
Existing PVC pipes are prone to scratches and cracks during handling and use, resulting in quality hazards and leakage. The existing self-repair technology is costly and has poor effect at room temperature.
A self-healing composite pipe with a three-layer structure is used. The outer and inner layers are made of high-content PVC resin and polyetheramine respectively. The middle layer is made of closed polyurethane and self-healing microcapsules, which are prepared through a three-layer co-extrusion process.
The bonding strength between the outer layer and the middle layer and the middle layer and the inner layer is significantly improved, achieving a self-healing effect at room temperature, avoiding further expansion of cracks, and improving the stability of the pipe.
Smart Images

Figure CN119022138B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of pipes and relates to a self-repairing composite pipe and a preparation method thereof. Background Art
[0002] PVC pipes are commonly used for water supply and drainage pipes. They have the characteristics of stable performance, easy installation, easy bonding, light weight, and low price. However, PVC pipes have poor scratch resistance and are prone to scratches on the outer surface during transportation or by impact from internal impact objects such as stones during delivery and drainage. The scratched parts are prone to further cracking, especially during the pressurization process, which will increase the size of the cracks and cause quality risks or leakage. Prior art Chinese patent CN117534921A "A self-repairing polyurethane toughened polyvinyl chloride composite material and its preparation method" discloses a self-repairing polyurethane toughened polyvinyl chloride composite material, which is prepared from the following components by weight: 50-70 parts of polyvinyl chloride, 10-40 parts of self-repairing polyurethane elastomer, 3-10 parts of compatibilizer, 2-10 parts of nanomaterial, 0.5-8 parts of coupling agent, 3-10 parts of plasticizer, 1-8 parts of heat stabilizer, 0.5-4 parts of lubricant, 0.5-3 parts of antioxidant, 0.5-2 parts of pigment, 0.5-2 parts of light stabilizer, and discloses that the tensile strength of the polyurethane elastomer is restored to 90% of the original after it is completely broken and repaired at 90°C for 1.5h. However, in the prior art, the self-repairing polyurethane elastomer needs to use expensive lithocholic acid, which will lead to a high cost of PVC composite materials, and the self-repairing performance at room temperature is not disclosed.
[0003] For this reason, there is an urgent need for a pipe that can achieve self-repair at room temperature. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a self-repairing composite pipe and a preparation method thereof.
[0005] The technical solution of the present invention is as follows:
[0006] A self-repairing composite pipe comprises an outer layer, an intermediate layer and an inner layer;
[0007] The raw material components of the outer layer include a first PVC resin and a first polyetheramine;
[0008] The raw material components of the intermediate layer include polyurethane and self-repairing microcapsules;
[0009] The self-repairing microcapsule has a core-shell structure, the core layer is a repair agent, and the shell layer is a coating layer;
[0010] The raw material components of the inner layer include a second PVC resin and a second polyetheramine.
[0011] Preferably, the weight of the first PVC resin in the outer layer is not less than 80%, and the weight of the second PVC resin in the inner layer is not less than 80%.
[0012] Preferably, the weight proportion of the first polyetheramine in the outer layer is not less than 2% and not more than 10%.
[0013] Preferably, the weight ratio of the polyurethane to the self-healing microcapsule is 100:1-10.
[0014] Preferably, the polyurethane is a blocked polyurethane.
[0015] More preferably, the blocking agent used for the blocked polyurethane is selected from one or a combination of phenol blocking agents, oxime blocking agents, alcohol blocking agents, amide blocking agents, imide blocking agents and pyrazole blocking agents.
[0016] Preferably, the repair agent is selected from adhesives.
[0017] Preferably, the weight proportion of the second polyetheramine in the inner layer is not less than 2% and not more than 10%.
[0018] Preferably, the average functionality of the first polyetheramine and the second polyetheramine is not less than 2.
[0019] A method for preparing the self-repairing composite pipe according to any one of the above embodiments comprises the following steps:
[0020] S1, respectively mixing the raw material components of the outer layer, the raw material components of the middle layer and the raw material components of the inner layer, and then melt-extruding and granulating them to prepare outer layer masterbatch, middle layer masterbatch and inner layer masterbatch;
[0021] S2. The outer layer masterbatch, the middle layer masterbatch and the inner layer masterbatch described in step S1 are co-extruded by a three-layer co-extrusion process to obtain the self-repairing composite pipe.
[0022] The beneficial effects of the present invention are:
[0023] (1) The composite pipe of the present invention adopts a three-layer structure of PVC-polyurethane-PVC, but the compatibility of polyurethane and PVC is poor, which will affect the bonding strength between the outer layer and the middle layer, and between the middle layer and the inner layer. In the present invention, the first polyetheramine and the second polyetheramine are added to the first PVC resin of the outer layer and the second PVC resin of the inner layer, respectively, which not only plays a role of plasticization, but also can significantly improve the bonding strength between the outer layer and the middle layer, and between the middle layer and the inner layer.
[0024] (2) In the composite pipe of the present invention, when the inner layer and / or the outer layer cracks, the self-repairing microcapsules in the middle layer will also rupture, and the repair agent in the core layer will flow out of the microcapsules and flow along the cracks and solidify, which can prevent the cracks from further expanding and repair the cracks, so that the composite pipe can still work normally.
[0025] (3) Furthermore, the polyurethane adopts a closed polyurethane, which can be unblocked at high temperature during polyurethane processing and re-release the isocyanate group. At the interface between the outer layer and the middle layer and at the interface between the middle layer and the inner layer, the amino groups of the isocyanate and the polyetheramine react, thereby improving the interface strength and making the composite pipe have better stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the structure of the self-repairing composite pipe of the present invention;
[0027] 1-outer layer, 2-middle layer, 3-inner layer, 4-self-healing microcapsules.
[0028] Figure 2 This is a cross-sectional view of the middle layer of the composite pipe of Example 1. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further illustrated and described below through specific implementation methods.
[0030] In order to solve the compatibility problem between the PVC layer and the polyurethane layer in the composite pipe and the self-repairing problem of the composite pipe, the present invention proposes a self-repairing composite pipe having a three-layer structure, including an outer layer 1, an intermediate layer 2 and an inner layer 3, wherein the inner layer 3 is located at the innermost layer of the self-repairing composite pipe, and the intermediate layer 2 is located between the outer layer 1 and the inner layer 3;
[0031] The raw material components of the outer layer 1 include a first PVC resin and a first polyetheramine; the main resin of the outer layer 1 is PVC resin, and the addition of the first polyetheramine can serve as a plasticizer for the first PVC resin and can also improve the compatibility between the outer layer 1 and the middle layer 2;
[0032] The raw material components of the intermediate layer 2 include polyurethane and self-repairing microcapsules;
[0033] The self-repairing microcapsules have a core-shell structure, with the core layer being the repair agent and the shell layer being the coating layer;
[0034] The middle layer is made of polyurethane as the main resin, and polyurethane has good impact resistance. When the composite pipe is impacted by external force, it can absorb part of the external force and improve the impact resistance of the composite pipe; when the composite pipe breaks or cracks appear, the cracks extend to the middle layer 2, and the self-repairing microcapsules are damaged by external forces, so that the repair agent inside is released, flows along the cracks or fractures, and repairs the cracks or fractures. In the present invention, the particle size of the self-repairing microcapsules can be 1-20μm, and the material of the coating layer is a polymer, which can be polyurea, polyurethane, polyamide, urea-formaldehyde resin, melamine resin, phenolic resin, polyacrylate resin, etc., without special restrictions. The self-repairing microcapsules can be prepared according to existing methods, such as CN116463106B, CN113845888B, CN113549429B, CN113583633B, CN112063371B, etc.
[0035] The raw material components of the inner layer 3 include a second PVC resin and a second polyetheramine; the main resin of the inner layer 3 is also a PVC resin, and the addition of the second polyetheramine can serve as a plasticizer for the second PVC resin and can also improve the compatibility between the inner layer 3 and the middle layer 2.
[0036] In the present invention, there is no particular limitation on the thickness of the outer layer 1, the middle layer 2 and the inner layer 3. From the perspective of practical use, the thickness of the outer layer 1 and the inner layer 3 can be 1 mm-5 cm, and the thickness of the middle layer can be 10 μm-2 mm.
[0037] In a preferred embodiment of the present invention, the weight proportion of the first PVC resin in the outer layer 1 is not less than 80%, and the weight proportion of the second PVC resin in the inner layer 3 is not less than 80%. The outer layer 1 and the inner layer 3 are both based on PVC resin. If the content of PVC resin is too low, the outer layer 1 and / or the inner layer 3 will be too soft or have insufficient performance. Furthermore, the weight proportion of the first PVC resin and the second PVC resin in the outer layer 1 and the inner layer 3, respectively, is not less than 85%. For example, the weight proportion can be any value of 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, etc., but is not limited to the above.
[0038] In a preferred embodiment of the present invention, the weight proportion of the first polyetheramine in the outer layer 1 is not less than 2% and not more than 10%. If the weight proportion of the first polyetheramine in the outer layer 1 is too low, it will affect the compatibility between the outer layer 1 and the middle layer 2, that is, the bonding strength is poor. For example, the weight proportion of the first polyetheramine in the outer layer 1 can be any value of 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., but is not limited to the above.
[0039] In the present invention, the raw material components of the outer layer 1 may also include plasticizers (such as TOTM, DOTP, etc.), fillers (such as kaolin, talc, light calcium carbonate, wollastonite, titanium dioxide, etc.), heat-resistant additives (such as calcium zinc stabilizers, barium zinc stabilizers, etc.), pigments (such as phthalocyanine blue, phthalocyanine green, carbon black), additives (such as dispersants, anti-aging agents, lubricants, etc.), impact modifiers (such as ACR impact modifiers, chlorinated polyethylene, etc.), which are well known to those skilled in the art.
[0040] In a preferred embodiment of the present invention, the weight ratio of polyurethane to self-repairing microcapsules is 100:1-10. If the content of self-repairing microcapsules in the middle layer 2 is too little, the self-repairing effect is poor; if the content of self-repairing microcapsules in the middle layer 2 is too high, the self-repairing microcapsules are easily squeezed against each other during processing, resulting in an increased probability of breakage, which affects the performance of the middle layer 2. For example, the weight ratio of polyurethane to self-repairing microcapsules can be any value of 100:1, 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10, etc., without special restrictions.
[0041] In a preferred embodiment of the present invention, the polyurethane is a blocked polyurethane. When a blocked polyurethane is used, during the processing, the blocked polyurethane is deblocked by heat, and the blocked -NCO group is released. At the interface between the outer layer 1 and the middle layer 2, and at the interface between the inner layer 3 and the middle layer 2, the reaction activity between the -NCO group and the -NH2 of the polyetheramine is very high (especially during co-extrusion molding, the temperature is very high and the reaction is faster), and a reaction can occur at the interface layer. The chemically bonded interface structure improves the interface bonding strength, so that the composite pipe of the present invention has better stability.
[0042] In a more preferred embodiment of the present invention, the blocking agent used in the blocked polyurethane is selected from one or a combination of phenol blocking agents, oxime blocking agents, alcohol blocking agents, amide blocking agents, imide blocking agents and pyrazole blocking agents. The melt processing temperature of polyurethane is very high, and the temperature of the melting section during molding is generally 180-230°C. When using blocked polyurethane, the blocking agent will be deblocked in the melting section and generate -NCO groups. Due to the existence of a certain interaction force between the extruded layers, the reaction between the -NCO group of the middle layer 2 and the -NH2 group of the inner layer 3 (or the outer layer 1) can be promoted, and a chemical reaction occurs at the interface, thereby improving the interfacial bonding strength. The deblocking temperature of phenolic blocking agents, such as phenol, is generally 140-150℃; the deblocking temperature of oxime blocking agents, such as methyl ethyl ketone oxime, is generally 140-150℃; the deblocking temperature of alcohol blocking agents, such as methanol and ethanol, is generally 180-185℃; the deblocking temperature of amide blocking agents, such as caprolactam, is generally 175-200℃; the deblocking temperature of pyrazole blocking agents is generally 130-150℃.
[0043] In a preferred embodiment of the present invention, the repairing agent is selected from adhesives, for example, acrylic adhesives, epoxy resin adhesives, chloroprene rubber adhesives and EVA adhesives, such as commercially available U-PVC adhesives. When the adhesive is used as the repairing agent, after the microcapsules are broken, the adhesive flows out and flows along the cracks, and the flowing adhesive gradually solidifies, repairing the cracks and preventing the cracks from further expanding.
[0044] In a preferred embodiment of the present invention, the weight proportion of the second polyetheramine in the inner layer 3 is not less than 2% and not more than 10%. If the weight proportion of the second polyetheramine in the inner layer 3 is too low, it will affect the compatibility between the inner layer 3 and the middle layer 2, that is, the bonding strength is poor. For example, the weight proportion of the second polyetheramine in the inner layer 3 can be any value of 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., but is not limited to the above.
[0045] In the present invention, the raw material components of the inner layer 3 may also include plasticizers (such as TOTM, DOTP, etc.), fillers (such as kaolin, talc, light calcium carbonate, wollastonite, titanium dioxide, etc.), heat-resistant additives (such as calcium zinc stabilizers, barium zinc stabilizers, etc.), pigments (such as phthalocyanine blue, phthalocyanine green, carbon black), additives (such as dispersants, anti-aging agents, lubricants, etc.), impact modifiers (such as ACR impact modifiers, chlorinated polyethylene, etc.), which are well known to those skilled in the art.
[0046] In a preferred embodiment of the present invention, the average functionality of each of the first polyetheramine and the second polyetheramine is not less than 2. If the average functionality of the first polyetheramine and the second polyetheramine is less than 2, it is not favorable for the reaction between the -NH2 group and the -NCO group at the interface, the reaction density is not high or the crosslinking density is low, which will result in little improvement in the interfacial bonding strength. For example, the average functionality of each of the first polyetheramine and the second polyetheramine can be any value of 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, etc., but there is no particular limitation. The first polyetheramine and the second polyetheramine of the present invention can be 3-functionality polyetheramines (such as polyetheramine T403), or composed of 3-functionality polyetheramines and 2-functionality polyetheramines (such as D230, D2000, D400, etc.), or composed of 4-functionality polyetheramines and 2-functionality polyetheramines.
[0047] The present invention also provides a method for preparing the self-repairing composite pipe described in any of the above embodiments, first preparing an outer layer masterbatch, an intermediate layer masterbatch and an inner layer masterbatch respectively, and then co-extruding by a three-layer co-extrusion molding process, specifically comprising the following steps:
[0048] S1, respectively mixing the raw material components of the outer layer 1, the raw material components of the middle layer 2 and the raw material components of the inner layer 3, and then melt-extruding and granulating them to prepare outer layer masterbatch, middle layer masterbatch and inner layer masterbatch;
[0049] S2, the outer layer masterbatch, the middle layer masterbatch and the inner layer masterbatch of step S1 are co-extruded by a three-layer co-extrusion process to obtain a self-repairing composite pipe.
[0050] In the composite pipe of the present invention, the following method can also be used: add the self-repairing microcapsules to the PVC resin to make a self-repairing PVC composite material masterbatch, and then prepare a self-repairing PVC layer. The self-repairing PVC layer can be made into a single-layer composite pipe, or the middle layer 2 can be replaced by the self-repairing PVC layer to form a three-layer structure of PVC-self-repairing PVC-PVC. Specifically, the self-repairing PVC composite material masterbatch can be prepared according to the following method: 100 parts of the third PVC resin, 2-10 parts of plasticizer (which can be TOTM, DOPT, epoxy soybean oil, polyether, etc.), 0-50 parts of filler, 0.5-1.5 parts of heat stabilizer, 0-5 parts of pigment, 1-10 parts of the above self-repairing microcapsules, and 0-5 parts of other additives (such as processing aid erucic acid amide, impact modifier, antioxidant, anti-ultraviolet agent, etc.) are mixed, added to a twin-screw extruder for melt extrusion and granulation, and the obtained product is obtained. When preparing a single-layer composite pipe, the self-repairing PVC composite masterbatch can be directly extruded and molded. When preparing a three-layer composite pipe, the outer layer masterbatch, the self-repairing PVC composite masterbatch and the inner layer masterbatch are co-extruded using a three-layer co-extrusion process. Whether it is a single-layer composite pipe or a three-layer composite pipe, since the pipe contains self-repairing microcapsules, it has self-repairing properties and can self-repair when ruptured or cracked. Compared with the above-mentioned PVC-polyurethane-PVC three-layer structure, the three-layer structure of PVC-self-repairing PVC-PVC has higher interlayer bonding strength because the main resins are all PVC resins, but the impact strength is poor and it is more susceptible to external impact and cracking.
[0051] The technical solution of the present invention is further described and illustrated according to various embodiments below. Unless otherwise specified, the parts described in the following embodiments are parts by weight.
[0052] Preparation Example 1-4 Preparation of PVC Masterbatch
[0053] Preparation Example 1
[0054] 90.8 parts of PVC resin (PVC-Ⅰ), 4 parts of polyetheramine T403, 4 parts of polyetheramine D2000 and 1.2 parts of barium zinc stabilizer were mixed and melt-extruded to prepare PVC masterbatch.
[0055] Preparation Example 2
[0056] 89.8 parts of PVC resin (PVC-Ⅰ), 1 part of polyetheramine T403, 1 part of polyetheramine D2000, 6 parts of DOTP plasticizer, 1.2 parts of barium zinc stabilizer and 1 part of polyethylene wax were mixed and melt-extruded to prepare PVC masterbatch.
[0057] Preparation Example 3
[0058] 89.8 parts of PVC resin (PVC-Ⅰ), 3 parts of polyetheramine D2000, 5 parts of DOTP plasticizer, 1.2 parts of barium zinc stabilizer and 1 part of polyethylene wax were mixed and melt-extruded to prepare PVC masterbatch.
[0059] Preparation Example 4
[0060] 89.8 parts of PVC resin (PVC-Ⅰ), 1 part of polyetheramine T403, 7 parts of DOTP plasticizer, 1.2 parts of barium zinc stabilizer and 1 part of polyethylene wax were mixed and melt-extruded to prepare PVC masterbatch.
[0061] Comparative Preparation Example 1
[0062] 89.8 parts of PVC resin (PVC-I), 8 parts of DOTP plasticizer, 1.2 parts of barium zinc stabilizer, and 1 part of polyethylene wax were mixed and melt-extruded to prepare PVC masterbatch.
[0063] Comparative Preparation Example 2
[0064] 89.8 parts of PVC resin (PVC-Ⅰ), 2 parts of polyethylene glycol 400, 6 parts of DOTP plasticizer, 1.2 parts of barium zinc stabilizer and 1 part of polyethylene wax were mixed and melt-extruded to prepare PVC masterbatch.
[0065] Preparation Example 5-7 Preparation of polyurethane masterbatch
[0066] Preparation Example 5
[0067] 10 parts of U-PVC adhesive, 3 parts of 1,3,5-benzenetricarboxylic acid chloride and 1 part of emulsifier (composed of OP-10 and sodium dodecylbenzene sulfonate in a weight ratio of 4:1) were mixed evenly, gradually added into water under high-speed stirring at 1500 rpm, and continued stirring at 600 rpm for 15 min. 5 parts of diethylenetriamine were added and continued stirring for 1 h. The filtered solid was washed twice with anhydrous ethanol and once with clean water, and dried in an oven at 60°C overnight to obtain self-healing microcapsules.
[0068] The reaction container was dried and dehydrated, and nitrogen was passed through for protection. 1 mol of IPDI and 1.02 mol of polycarbonate diol (Mn=1500) were added to the reaction container, and stirred at room temperature for 1 hour. The temperature was continued to rise to 80°C and reacted for 2 hours. 2 g of dibutyltin dilaurate was added and the reaction was continued for 2 hours to obtain polyurethane.
[0069] 100 parts of the above polyurethane and 2 parts of the above self-repairing microcapsules were mixed and melt-extruded to obtain a polyurethane masterbatch.
[0070] Preparation Example 6
[0071] The reaction container was dried and dehydrated, and nitrogen was passed through for protection. 1 mol part of IPDI and 0.9 mol part of polycarbonate diol (Mn=1500) were added into the reaction container, and stirred at room temperature for 1 hour. The temperature was continued to rise to 80°C for reaction for 2 hours. 2 g of dibutyltin dilaurate was added and the reaction was continued for 2 hours. 0.8 mol part of anhydrous ethanol was added and the reaction was continued for 2 hours. The unreacted anhydrous ethanol was removed to obtain a closed polyurethane.
[0072] 100 parts of the above-mentioned blocked polyurethane and 5 parts of the self-repairing microcapsules of Preparation Example 5 were mixed and melt-extruded to obtain a polyurethane masterbatch.
[0073] Preparation Example 7
[0074] The difference between Preparation Example 7 and Preparation Example 6 is that in Preparation Example 6, anhydrous ethanol is replaced by an equal molar amount of methyl ethyl ketone oxime, and the self-healing microcapsules in Preparation Example 5 are adjusted from 5 parts to 10 parts. The other steps remain unchanged.
[0075] Example 1
[0076] The PVC masterbatch of Preparation Example 1 and the polyurethane masterbatch of Preparation Example 5 were co-extruded using a three-layer co-extrusion process to obtain a self-repairing composite pipe with an inner layer of PVC, a middle layer of self-repairing polyurethane, and an outer layer of PVC. The inner diameter was 2 cm, the inner layer thickness was 5 mm, the middle layer thickness was 1 mm, and the outer layer thickness was 5 mm.
[0077] Example 2
[0078] The difference between Example 2 and Example 1 is that in Example 1, the polyurethane masterbatch of Preparation Example 5 is replaced by the polyurethane masterbatch of Preparation Example 6. The other steps remain unchanged.
[0079] Example 3
[0080] The difference between Example 3 and Example 1 is that in Example 1, the polyurethane masterbatch of Preparation Example 5 is replaced by the polyurethane masterbatch of Preparation Example 7. The remaining steps remain unchanged.
[0081] Example 4
[0082] The difference between Example 4 and Example 2 is that in Example 2, the PVC masterbatch of Preparation Example 1 is replaced by the PVC masterbatch of Preparation Example 2. The other steps remain unchanged.
[0083] Example 5
[0084] The difference between Example 5 and Example 2 is that in Example 2, the PVC masterbatch of Preparation Example 1 is replaced by the PVC masterbatch of Preparation Example 3. The other steps remain unchanged.
[0085] Example 6
[0086] The difference between Example 6 and Example 2 is that in Example 2, the PVC masterbatch of Preparation Example 1 is replaced by the PVC masterbatch of Preparation Example 4. The other steps remain unchanged.
[0087] Example 7
[0088] The difference between Example 7 and Example 1 is that in Example 1, the PVC masterbatch of Preparation Example 1 is replaced by the PVC masterbatch of Preparation Example 4. The other steps remain unchanged.
[0089] Comparative Example 1
[0090] The difference between Comparative Example 1 and Example 1 is that in Example 1, the PVC masterbatch of Preparation Example 1 is replaced by the PVC masterbatch of Comparative Preparation Example 1. The remaining steps remain unchanged.
[0091] Comparative Example 2
[0092] The difference between Comparative Example 2 and Example 1 is that in Example 1, the PVC masterbatch of Preparation Example 1 is replaced by the PVC masterbatch of Comparative Preparation Example 2. The remaining steps remain unchanged.
[0093] Comparative Example 3
[0094] The difference between Comparative Example 3 and Example 2 is that in Example 2, the PVC masterbatch of Preparation Example 1 is replaced by the PVC masterbatch of Comparative Preparation Example 2. The remaining steps remain unchanged.
[0095] Comparative Example 4
[0096] The difference between Comparative Example 4 and Example 1 is that in Example 1, the polyurethane masterbatch of Preparation Example 5 is replaced by the polyurethane obtained in Preparation Example 5 (ie, no self-healing microcapsules are added). The remaining steps remain unchanged.
[0097] Example 8
[0098] The PVC masterbatch of Preparation Example 1, the PVC masterbatch of Preparation Example 2 and the polyurethane masterbatch of Preparation Example 5 were co-extruded using a three-layer co-extrusion process to obtain a self-repairing composite pipe with an inner layer of PVC (PVC masterbatch of Preparation Example 1), a middle layer of self-repairing polyurethane, and an outer layer of PVC (PVC masterbatch of Preparation Example 2), with an inner diameter of 1.5 cm, an inner layer thickness of 3 mm, a middle layer thickness of 0.5 mm, and an outer layer thickness of 5 mm.
[0099] Example 9
[0100] The difference between Example 9 and Example 8 is that in Example 8, the polyurethane masterbatch of Preparation Example 5 is replaced by the polyurethane masterbatch of Preparation Example 6. The remaining steps remain unchanged.
[0101] The performance test results are shown in Table 1 below.
[0102] Interlayer peeling strength grade: Grade 1, >3MPa; Grade 2, >2MPa, ≤3MPa; Grade 3, >1MPa, ≤2MPa; Grade 4, >0.3MPa, ≤1MPa; Grade 5, ≤0.3MPa.
[0103] A No. 11 scalpel was used to penetrate the composite pipe with a blade length of 2 cm. The pipe was placed at room temperature for 24 hours to test the recovery rate of interlayer peel strength. A recovery rate of more than 80% was considered good, a recovery rate of 60% to 80% was considered qualified, and a recovery rate of less than 60% was considered unqualified.
[0104] The recovery rate of interlayer peel strength = interlayer peel strength 24 hours after the knife edge penetrates / initial interlayer peel strength × 100%.
[0105] Table 1 Performance test results
[0106]
[0107] From the data results in Table 1 above, it can be seen that the composite pipe of the present invention has good interlayer bonding strength and self-healing performance. If the polyetheramine in the inner layer or outer layer is replaced with polyethylene glycol, the bonding strength is significantly lower. This may be because the hydrogen bonding effect between the hydroxyl group in polyethylene glycol and the urethane bond of the polyurethane is not strong, while the hydrogen bonding effect between the amino group in the polyetheramine and the urethane bond of the polyurethane is strong, which can form a certain hydrogen bonding effect at the interface, thereby improving the interfacial bonding strength.
[0108] As described above, the basic principles, main features and advantages of the present invention are shown and described. Those skilled in the art should understand that the present invention is not limited by the above embodiments, which are only preferred embodiments of the present invention and cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the scope of the present invention and the content of the specification should still be within the scope of the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents.
Claims
1. A self-repairing composite pipe, characterized in that: It comprises an outer layer (1), a middle layer (2) and an inner layer (3); The raw material components of the outer layer (1) include a first PVC resin and a first polyetheramine; The raw material components of the intermediate layer (2) include polyurethane and self-repairing microcapsules; The polyurethane is a closed polyurethane; The self-repairing microcapsule has a core-shell structure, the core layer is a repair agent, and the shell layer is a coating layer; The raw material components of the inner layer (3) include a second PVC resin and a second polyetheramine.
2. The self-repairing composite pipe according to claim 1, characterized in that: The weight proportion of the first PVC resin in the outer layer (1) is not less than 80%, and the weight proportion of the second PVC resin in the inner layer (3) is not less than 80%.
3. The self-repairing composite pipe according to claim 1, characterized in that: The weight proportion of the first polyetheramine in the outer layer (1) is not less than 2% and not more than 10%.
4. The self-repairing composite pipe according to claim 1, characterized in that: The weight ratio of the polyurethane to the self-repairing microcapsule is 100:1-10.
5. The self-repairing composite pipe according to claim 1, characterized in that: The blocking agent used for the blocked polyurethane is selected from one or a combination of phenol blocking agents, oxime blocking agents, alcohol blocking agents, amide blocking agents, imide blocking agents and pyrazole blocking agents.
6. The self-repairing composite pipe according to claim 1, characterized in that: The repair agent is selected from adhesives.
7. The self-repairing composite pipe according to claim 1, characterized in that: The weight proportion of the second polyetheramine in the inner layer (3) is not less than 2% and not more than 10%.
8. The self-repairing composite pipe according to claim 1, characterized in that: The average functionality of each of the first polyetheramine and the second polyetheramine is not less than 2.
9. A method for preparing the self-repairing composite pipe according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, respectively mixing the raw material components of the outer layer (1), the raw material components of the middle layer (2) and the raw material components of the inner layer (3), and then melt-extruding and granulating them to prepare outer layer masterbatch, middle layer masterbatch and inner layer masterbatch; S2. The outer layer masterbatch, the middle layer masterbatch and the inner layer masterbatch described in step S1 are co-extruded by a three-layer co-extrusion process to obtain the self-repairing composite pipe.
Citation Information
Patent Citations
A method for preparing phase change energy storage microcapsules that can be used in fabrics and the microcapsules themselves.
CN112063371B
A controllable supercooling phase change microcapsule, its preparation method and application
CN113549429B
A method for preparing phase change microcapsules with high encapsulation rate
CN113583633B
Phase-change microcapsule and heat exchange fluid containing the same
CN113845888B
A phase change temperature-regulating microcapsule for textiles and its preparation method
CN116463106B